ICT Competencies among Public Secondary School MAPEH Teachers: An Assessment - Samonte, Kenneth; de Guzman, Pastora (JPAIR Institutional Research, 2019)
The impact of Information and Communication Technology (ICT) has been felt in the educational school setting locally and internationally. It plays a vital role both in teaching and learning. This study aimed to assess the ICT competencies among MAPEH teachers of selected Public Secondary Schools in District IV of Nueva Ecija. Specifically, it aimed to (1) determine the profile of the MAPEH teachers; and (2) assess their level of ICT competencies in terms of technology operations and concepts and pedagogical skills. The researchers used the descriptive research method, specifically questionnaires, as the primary tool for data gathering. Thirty Four (34) MAPEH teachers served as respondents. Frequency, percentage, and the weighted mean were used in this study. Results showed that respondents assessed their ICT competencies as "advanced" in terms of technology operations and concepts, and evaluated their pedagogical competence as "basic." Respondents have basic knowledge of ICT. Conversely, this is not enough to say that MAPEH teachers are already competent and skilled in ICT. Teacher professional development is a critical factor in the successful integration of computers in teaching. It is recommended that administrators must allocate a budget for ICT, most notably on the technological resources, and teachers shall undergo seminars and training that will help further enhance and improve their computer skills and knowledge.